Communicating bad news in the practice of nursing: an integrative review - Agnese,Beatriz Lopes (2022)
ABSTRACT Objective To analyze current scientific knowledge about communication of bad news by nurses. Methods This is an integrative literature review carried out by searching articles published in national and international journals indexed at SciELO, MEDLINE® (PubMed®), Scopus, Bireme and CINAHL, from 2010 to 2020, by crossing the controlled descriptors “communication”, “revelation of the truth”, and “nursing”, and the uncontrolled descriptor “bad news”. Results Ten articles with qualitative and cross-sectional design, as well as case reports were included. The analysis indicated the evidence available in the literature showed the nurses’ lack of ability to communicate bad news, although they are professionals who have close contact with patients and families and who establish a strong bond with them, and often face challenging situations for communicating bad news. Conclusion There is an evident need to invest in training of nurses on skills to communicate bad news and establish a nurse-patient bond when dialoguing with the family. There are few studies in the literature addressing this issue; therefore, it is recommended to perform research that can contribute to improvements in the clinical practice and developing protocols to promote such care.